Nutrient fluxes from rivers, groundwater, and the ocean into the coastal embayment along the Sanriku ria coast, Japan. Issue 7 (14th May 2021) - Nakajima, Toshimi; Sugimoto, Ryo; Kusunoki, Takahiro; Yokoyama, Katsuhide; Taniguchi, Makoto
Abstract: External nutrient supply from the land and ocean is crucial for sustaining high primary productivity in coastal seas. Submarine groundwater discharge (SGD) is recognized as one of the most important sources of terrestrial nutrients. However, the relative importance of SGD‐derived nutrients from different sources in coastal ecosystems controlled by offshore exchange has not been well quantified. Here, we assessed water and nutrient budgets in the semi‐enclosed bay along the Sanriku ria coast, where the intrusion of nutrient‐enriched oceanic water is substantial. We conducted seasonal sampling campaigns and monitored the groundwater level throughout the year. Water and nutrient fluxes from fresh groundwater, saline groundwater, river water, and oceanic water were estimated using a hydrological method and radium (Ra) mass balance model. The results indicated that oceanic water was a dominant source, accounting for 99.5%, 86%, 97%, and 84% of the total influx of water, dissolved inorganic nitrogen, dissolved inorganic phosphorus, and dissolved silica, respectively. Although the mean fluxes of land‐derived nutrients were small, the contribution increased to 28–59% in October, when nutrient fluxes of oceanic water weakened. Of the terrestrial sources, SGD dominated (41–94%), particularly saline SGD (>99% of total SGD). We concluded that an efficient supply of the primary limiting nutrient from land to the coastal ecosystem can accelerate coastal primary production during certain seasons, even if oceanic nutrients are typically the dominant source.